A multidisciplinary approach for prenatal diagnosis of FRASER SYNDROME-report of a novel variant in FRAS1 - Jyothsna Madan; Mitesh Shetty; B.S. Ramamurthy; Surekha Managoli (Elsevier, 2022)
Objective: With this case report, we would like to highlight the importance of a multidisciplinary approach and atypical findings of congenital high airway obstruction sequence (CHAOS), anhydramnios, and renal dysgenesis in the prenatal diagnosis of Fraser syndrome (FS). Case report: A 25-year-old primigravida at 19 weeks of routine anomaly scan revealed abnormal sonographic findings such as fetal bilateral dysplastic small kidneys and gross oligohydramnios. The further detailed evaluation revealed that both fetal lungs were hyperechogenic with prominent (dilated) trachea and bronchi suggestive of CHAOS. Based on these findings, a diagnosis of FS was suspected. The couple was counseled and the pregnancy was terminated. The postmortem evaluation and novel homozygous variant in the FRAS1 gene confirmed the diagnosis of FS. Conclusion: The diagnosis and counseling of the patient were supported by a well-coordinated, multidisciplinary approach involving an obstetrician, a fetal medicine specialist, a medical geneticist, and a fetal pathologist.